Strength of Hollow Compressed Stabilized Earth-Block Masonry Prisms - Xinlei Yang; Hailiang Wang (Advances in Civil Engineering)
Earth represents an ecological building material that is thought to reduce the carbon footprint at a point in its life cycle. However, it is very important to eliminate the undesirable properties of soil in an environmentally friendly way. Cement-stabilized rammed earth, as a building material, has gradually gained popularity due to its higher and faster strength gain, durability, and availability with a low percentage of cement. This paper covers a detailed study of hollow compressed cement-stabilized earth-block masonry prisms to establish the strength properties of hollow compressed cement-stabilized earth-block masonry. The test results for masonry prisms constructed with hollow compressed cement-stabilized blocks with two different strength grades and two earth mortars with different strengths are discussed.